Naissance de la didactique de la géographie et modernisation de la géographie scolaire (des années 1965 à 1995) - Micheline Roumégous (Bulletin de l’Association de Géographes Français)
After a period of reflexion on the part of teachers, encouraged by the enthousiasm for reform of “68”, a new definition of school geography to be taught in primary schools emerged as an “awakening to the world”. This renovation of school geography and the invention of its didactics took shape after “81”, with the desire of a left-wing government to radically modernise radically the imparted knowledge and to reform the way pupils were taught. Those who trained the teachers, feeling supported by this, focused on a “new” academic geography whose objects and methods had been redefined in the seventies, to invent a teaching approach which would make easy to convey its social relevance and to renew the epistemology of school geography. In this way primary sschool geography became part of an intellectual process shared with other academic fields, perhaps as the “intuitive approach to teaching” had envisioned it in the 1850s when they were invented.